Multi-criteria research lines on livestock manure biorefinery development towards a circular economy: From the perspective of a life cycle assessment and business models strategies. (20th March 2022) - Awasthi, Sanjeev Kumar; Kumar, Manish; Sarsaiya, Surendra; Ahluwalia, Vivek; Chen, Hongyu; Kaur, Guneet; Sirohi, Ranjna; Sindhu, Raveendran; Binod, Parameswaran; Pandey, Ashok; Rathour, Rashmi; Kumar, Sunil; et al.
Abstract: Livestock manure (LSM) is a profitable waste if handled sensibly, but simultaneously it imposes several environmental and health impacts if managed improperly. Several approaches have been adopted globally to cartel the problem associated with LSM management and recovery of value-added products, still, technological innovation needs further upgradation in consideration with the environment, energy, and economy. This review delivered a vibrant portrait of manure management, which includes, bioenergy generation and resource recovery strategies, their current scenario, opportunities, challenges, and prospects for future researches along with global regulations and policies. Several bioenergy generation and nutrient recoveries technologies have been discussed in details, still, the major glitches allied with these technologies are its high establishment costs, operational costs, manure assortment, and digestate handling. This review also discussed the techno-economic assessment (TEA) and life cycle assessment (LCA) of LSM management operation in the context of their economical and environmental sustainability. Still, extensive researches needed to build an efficient manure management framework to advance the integrated bioenergy production, nutrients recycling, and digestate utilization with least environmental impacts and maximal economical gain, which has critically discussed in the current review. Graphical abstract: Image 1 Highlights: Improper livestock manure management imposes several health problems. Proper livestock manure management enable to replace 60–75% synthetic fertilizer. Anaerobic digestion and composting are most effective manure management strategies. Integration of technologies are necessary for proper livestock manure management.